Operational Customer Relationship Management Pada Sari Good Bakery - Aziz, Ghani; Hasugian, Leonardi Paris (PETIR, 2019)
Current customer service at Sari Good Bakery is still done simply. Product promotion is done by placing banners on their store, then doing promotion by word of mouth so that products tend to be only known by the people around the store and the promotion tend to flow slowly. Then to deliver customer comments through face to face directly or by telephone or SMS. This method sometimes results in forgotten comments due to unavailability of facilities to accommodate these comments so it has potential of customers decreases. The solution to overcome this problem is by building Operational Customer Relationship Management. The method used in this research is a descriptive qualitative method by doing interviews and observations. This Operational CRM uses the Object Oriented Programming approach and uses prototype development methods. Operational CRM that is built can improve customer service such as conducting promotions widely and storing feedback on the website.